Multistage delivery of CDs-DOX/ICG-loaded liposome for highly penetration and effective chemo-photothermal combination therapy - Xiao Xue; Ting Fang; Luyao Yin; Jianqi Jiang; Yunpeng He; Yinghui Dai; Dongkai Wang (Taylor & Francis Group, 2018)
Nanoparticles (NPs) have proven to be effective drug carriers in diagnosis and therapy of cancer. But, they faced a contradictory issue that NPs with large size appear weak tumor penetration, meanwhile small size resulted in poor tumor retention. Herein, we fabricated doxorubicin conjugated carbon dots (CDs-DOX) and indocyanine green (ICG)-loaded liposomes (ICG-LPs) named CDs-ICG-LPs using a modified reverse phase evaporation process, and with high incorporation in the aqueous core. The CDs-ICG-LPs exhibited good monodispersity, excellent fluorescence/size stability, and consistent spectra characteristics compared with free ICG or DOX. Moreover, the CDs-ICG-LPs showed higher temperature response, faster DOX release under laser irradiation. In the meantime, the fluorescence of DOX and ICG in CDs-ICG-LPs was also visualized for the process of subcellular location in vitro. In comparison with chemo or photothermal treatment alone, the combined treatment of CDs-ICG-LPs with laser irradiation synergistically induced the apoptosis and death of DOX-sensitive HepG2 cells. In vivo antitumor activities demonstrated CDs-ICG-LPs could reach higher antitumor activity compared with CDs-DOX and ICG-LPs for H22 tumor cells, and suppressed H22 tumor growth in vivo. Notably, no systemic toxicity occurrence was observed after repeated dose of CDs-ICG-LPs with laser irradiation. Hence, the well-defined CDs-ICG-LPs exhibited great potential in targeting cancer imaging and chemo-photothermal therapy.